Les nouvelles formes de hockeyisation de Montréal… ou quand le sport professionnel « développe » la ville - Fannie Valois-Nadeau (Communiquer)
This article explores the Montreal’s hockeyisation process from two recent projects initiated by the Montreal Canadiens hockey club; the donation of refrigerated public rinks to so-called disadvantaged neighbourhoods and the construction of real estate towers in the downtown. The purpose is to identify how this professional sport team takes place in the city by the funding of projects that go beyond the entertainment industry. Based on a case study, this article highlights the new roles played by sports industries and the underlying discourses on city development and corporate social responsibility. In the wake of cultural studies and sport sociology researches that critically interrogated the cultural economies of entertainment, the following analysis shows the growing weight of the professional sports teams within cities.